HUBUNGAN WAKTU PENYEDIAAN DOKUMEN REKAM MEDIS DENGAN LOYALITAS PASIEN DI POLIKLINIK PENYAKIT DALAM DI RUMAH SAKIT UMUM SEMBIRING DELI TUA TAHUN 2021 - Afrilius Simanjuntak (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
Standards service minimum are provisions regarding the type and quality of basic services which are mandatory regional affairs that every citizen has the right to obtain at a minimum. One of the minimum service standards in the medical record unit is that the time for providing outpatient medical record documents is 10 minutes which is calculated for the time for providing medical record documents starting from the patient registering until the medical record document is provided/found by the officer. The length of time a patient waits is one of the potential indicators that can affect patient loyalty to the hospital. The is purpose study to analyze the relation between the time of providing medical record documents with patient loyalty at the Internal Medicine Polyclinic of Sembiring Deli Tua General Hospital. This type of research is an analytic study with a cross sectional design. Data were analyzed by univariate and bivariate analysis using chi square (x) test. The number of samples available as many as 64 samples were taken from the population, namely internal polyclinic patients. The results of the bivariate analysis of the time of providing medical record documents with patient loyalty obtained a p value of 0.001. From the results of the bivariate analysis p value < 0.05, there is a relationship between the time of providing medical record documents with patient loyalty at the Internal Medicine Polyclinic of Sembiring Deli Tua General Hospital. it is hoped that the hospital management will conduct socialization to service officers to provide excellent service, it aims to improve the quality of service in the hospital.